Time-efficient consultation hours in the department of gynecological endocrinology - Berger, Anne-Sophie; Sourouni, Marina; Bitterlich, Norman; Blickenstorfer, Kerstin; Bühling, Kai J.; Lambrinoudaki, Irene; Ruan, Xiangyan; Schaudig, Katrin; von Wolff, Michael; Stute, Petra (Gynecological endocrinology, 2024)
The aim was to conduct a benchmark pilot study to find the best practice for consultation hours in the field of gynecological endocrinology. Suitable benchmarking participants were found in China, Germany, Greece, and Switzerland. Specifically, the study aimed to find the most time-efficient and beneficial consultation type in gynecological endocrinology focused on menopause and whether a shorter face-to-face consultation correlates with lower patient satisfaction. This was an observational study. To analyze the processes of all benchmarking participants three tools were used: a measurement of time needed for the different consultation types, a questionnaire for patients and one for physicians. The primary endpoint was the time measurement of first consultations. Secondary endpoints were the time measurements of follow-up consultations and phone consultations and patient satisfaction. The mean overall duration of a first consultation differed from 20.4 min to 39.7 min (p = 0.003), mainly based on differences of the mean time to acquire the patient history, 5.6 to 21.6 min (p < 0.001). The percentage of patients who felt they had enough time to discuss questions ranged from 70% to 100% (p < 0.001). The percentage of patients who felt fully understood by their physician ranged from 62.5% to 92% (p = 0.006). The duration of a first consultation did not correlate with patients feeling well consulted (r=-0.048, p = 0.557). A concise patient history that concentrates on the most relevant points can reduce the total consultation time. Reducing consultation time can be made without compromising how well patients feel consulted.
Online veröffentlicht: 27. August 2024
Gesehen am 23.10.2024